THE EUROPEAN UNION EXPOSED TO THE RISK OF THE SOVEREIGN DEBT CRISIS. CASE STUDY: SPAIN AND PORTUGAL - Ioana-Iulica, MIHAI (Strategii Manageriale, 2013)
The global economic crisis, intensely debated, started almost six years ago, subjected the EU to new resistance tests because of the macroeconomic imbalances in the Euro Zone, generated by the increase of sovereign debts, especially in the PIIGS countries (Portugal, Ireland, Italy, Greece, Spain). The situation has degenerated because of the lack of legal leverages through which the member countries should be forced to correct the fiscal imbalances and to meet the macroeconomic convergence criteria imposed. The Treaty on Fiscal Governance in the EU, signed on 2 March 2012, appears to be the key to the macroeconomic recovery in the Euro Zone, due to the more severe budgetary discipline it imposes. This paper, by means of deductive analysis and causal explanations, outlines the current economic situation of the Euro Zone, under the impact of the member countries’ sovereign debt crisis, focusing on Spain and Portugal. In addition to reliable statistics, the paper also presents the EU’s economic recovery strategy that anticipates its future. Unfortunately, the perspective of the Euro Zone is still in a fairly high degree of uncertainty, strongly influenced by the economic development of the member countries and by solving the problems they face. Spain and Portugal are the actual example.